Single nucleotide variants rs6582147, rs10010305, rs2136810, rs17797829 as new molecular genetic markers of sudden cardiac death - A. A. Ivanova; V. N. Maksimov; D. I. Moiseeva; S. K. Malyutina; V. P. Novoselov; M. I. Voevoda (Российский кардиологический журнал, 2018)
Aim. To confirm association between sudden cardiac death (SCD) and single nucleotide polymorphisms rs6582147 rs 10010305, rs2136810, rs17797829, identified as the most likely candidate markers.Material and methods. The SCD group (n=360, mean age 53,0±9,2 years, men — 76,9%, women — 23,1%) was formed using the SCD criteria of the European Society of Cardiology. The control group (n=402, mean age 52,9±9,1 years, men — 69,7%, women — 30,3%) was selected by gender and age from the DNA bank of international studies MONICA, HAPIEE. DNA is separated by phenol-chloroform extraction. Genotyping was performed by polymerase chain reaction followed by analysis of restriction fragment length polymorphism.Results. The GT rs6582147 genotype is associated with a protective effect on SCD (OR=0,671, 95% CI 0,496-0,909, p=0,011), and the GG genotype with an increased risk of SCD (OR=1,598, 95% CI 1,195-2,135, p=0,002). The greatest effect was in the group of men over 50 years old (p<0,05). The CT rs10010305 genotype is associated with SCD in the group of men (OR=1,773, 95% CI 1,085-2,897 p=0,027), in the group of men over 50 years old (p<0,05) and in the group of people over 50 years old without separation according to sex (OR=1,719, 95% CI 1,038-2,847 p=0,041). The GG rs2136810 genotype is associated with an increased risk of SCD (OR=1,372, 95% CI 1,005-1,871, p=0,049); in the group of people over 50, the GA rs2136810 genotype is associated with a protective effect against SCD (OR=0,642, 95% CI 0,422-0,976, p=0,045). In the group of women, the GG rs17797829 genotype is protective for SCD (OR=0,392, 95% CI 0,203-0,760, p=0,007), in the group of women over 50, except for the GG genotype, the AA genotype of the same polymorphism is associated (OR=2,739, 95% CI 2,176-3,448, p=0,020).Conclusion. According to the results of study, single nucleotide polymorphisms rs6582147 rs10010305, rs2136810, rs17797829 confirmed the association with SCD.